How to develop self-confidence & influence people by public speaking - Carnegie, Dale, 1888-1955 (New York : Gallery Books, an imprint of Simon & Schuster, Inc., 2017)
Drawing on Dale Carnegie's years of experience as a business trainer this book will show you how to overcome the natural fear of public speaking, to become a successful speaker and even learn to enjoy it.
Developing courage and self-confidence -- Self-confidence through preparation -- How famous speakers prepared their addresses -- The improvement of memory -- Essential elements in successful speaking -- The secret of good delivery -- Platform presence and personality -- How to open a talk -- How to close a talk -- How to make your meaning clear -- How to interest your audience -- Improving your diction -- Appendix: Speech building with exercises.
Keywords: Public speaking; Business presentations; Oral communication; Self-confidence.; Self-actualization (Psychology); Work-life balance